2006
DOI: 10.1029/2005gc001048
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐silicate segregation in deforming dunitic rocks

Abstract: [1] We report the results of an investigation of the microstructural evolution of rocks composed of a silicate plus a molten metal sulfide phase deformed plastically in simple shear. Deformation experiments on samples of San Carlos olivine (Fo 90 ) + 3, 5, or 9 vol% iron sulfide reveal the segregation of iron sulfide melt from the solid polycrystalline olivine matrix into regions enriched in metallic melt separated by regions depleted in the metallic melt. Previously published experimental studies on core-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…Oxygen fugacity during hot-pressing and deformation was fixed within the olivine stability field by oxidation of the Ni capsule. A schematic drawing of the piston arrangement is shown by Hustoft and Kohlstedt (2006), and details of the deformation assembly are given by Mei and Kohlstedt (2000b) and Zimmerman and Kohlstedt (2004).…”
Section: Creep Experimentsmentioning
confidence: 99%
“…Oxygen fugacity during hot-pressing and deformation was fixed within the olivine stability field by oxidation of the Ni capsule. A schematic drawing of the piston arrangement is shown by Hustoft and Kohlstedt (2006), and details of the deformation assembly are given by Mei and Kohlstedt (2000b) and Zimmerman and Kohlstedt (2004).…”
Section: Creep Experimentsmentioning
confidence: 99%
“…Although the general spherical shape of the liq- uid pockets and the smoothly curved grain boundaries indicate a locally equilibrated microstructure, the static sulphide liquid distribution does not represent a true textural equilibrium, as the lowest energy would be attained by complete removal of the sulphide liquid from the system (e.g. Jurewicz and Watson, 1985). The distribution rather reflects the particular starting mixture, a low liquid pocket mobility, and the annealing time.…”
Section: Static Experimentsmentioning
confidence: 99%
“…Grain-scale percolation of an interconnected Fe-S liquid through a solid silicate matrix has long been suggested to be an important mechanism of planetary differentiation (Bruhn et al, 2000;Yoshino et al, 2003;Hustoft and Kohlstedt, 2006;Terasaki et al, 2008). This differentiation mechanism has recently gained credibility due to the study of Kruijer et al (2014) that showed that the time of differentiation of iron meteorites correlates with the sulphur content in the iron.…”
Section: Differentiation After Crossing the Sulphide Solidusmentioning
confidence: 99%
See 2 more Smart Citations